Prevalence of Gastrointestinal Parasitic Infections of Goats in Nongchok District, Bangkok Checked by Modified Formalin-ether Sedimentation and McMaster Technique - Khumpool, Grisada (Journal of Mahanakorn Veterinary Medicine, 2018)
This study aimed to investigate the prevalence of internal parasitic infection using modified formalin –ether sedimentation and McMaster technique for fecal examination of 483 goats the feces were collected from Nongchok subprovince of Thailand during December 2013 to June 2014. The results revealed that seven characters of internal parasitic infections included Strongyle-type egg (40.6%), Strongyle-type egg and Eimeria oocyst (20.5%), Strongyle-type egg and Monezia expansa egg (4.9%), Eimeria oocyst (18.4%), M. expansa egg and Eimeria oocyst (1.2%), Strongyle-type egg, M. expansa egg and Eimeria oocyst (3.7%) and M. expansa egg (10.7%). This technique could identify and count the parasitic eggs, simultaneously. The internal parasite egg counts per gram of feces (EPG) of all characters were also reported.